ANALISIS FAKTOR RISIKO DAN PENCEGAHAN JANTUNG KORONER DAN STROKE: TINJAUAN LITERATUR - Khairuman; Alfarizi; Aminah; Syifa Zahara; ⁠Cut Risi Rayyana; Salwatun Ahzan; Ana Khaira; Nurul Faizah; Tomi Saputra; Ikmal (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
Coronary heart disease (CHD) and stroke are two leading causes of global morbidity and mortality. The main risk factors contributing to the incidence of CHD and stroke include hypertension, dyslipidemia, obesity, diabetes mellitus, and unhealthy lifestyles such as smoking and lack of physical activity. This study employs a literature review method to analyze various risk factors and preventive strategies identified in previous studies. The analysis results indicate that hypertension is the most dominant risk factor for stroke, while dyslipidemia and smoking habits significantly contribute to the development of CHD. Additionally, genetic and socioeconomic factors exacerbate conditions in high-risk patients. Effective prevention strategies involve a multidisciplinary approach, including early detection, medical interventions, healthy lifestyle promotion, and public health policies. Several studies emphasize that lifestyle modifications, such as increased physical activity and dietary changes, can significantly reduce the risk of CHD and stroke. The findings of this study highlight the importance of sustainable preventive efforts to reduce the incidence of cardiovascular diseases in society